Personal features and well-being as predictors of meaning in life among people living with HIV/AIDS (PLWHAS) in Nigeria (2016)
satisfaction and hopelessness as predictors of meaning in life among people living with HIV/ AIDS. Methods: Two hundred patients; 126 females and 74 males, aged between 17 and 70 years were used for the study. Their mean age was 38.9 years with a standard deviation of 10.2 years. Results: The findings revealed that self-esteem, life satisfaction and hopelessness significantly predicted meaning in life and they are important constructs in assessing meaning in the lives of PLWHAs. Conclusion: Therefore, it was recommended that meaning centered therapy programs should be put in place by health care givers and other stakeholders dealing with PLWHAs to increase patient’s meaning in life